Analisis Dampak Pengguna Sosial Media Terhadap Produktivitas Akademik Mahasiswa - Tanjung Lasmana,; Ayunda Khoiriyati, (Jurnal Publikasi Ilmu Manajemen, 2025)
This research was conducted with the aim of finding out the impact of social media use on student academic productivity and how to overcome dependence. This type of research is a qualitative research with an interview method. With a data collection technique carried out through direct conversations between researchers and respondents, the purpose of this interview is to obtain deeper and more detailed information. The most widely used social media are whatsapp, Instagram, tiktok, youtobe, facebook, blogger and twitter. Students tend to get bored when they don't use social media because each social media has advantages that make its users. The intensity of social media use averages more than 4 hours a day and the medium used to access the social media is a smartphone. The impact of social media students use social media to get information about knowledge, tips and tricks for learning that make it easier to do assignments so as to support their achievements. The way students can overcome learning dependence on social media is by managing or managing time well, limiting the use of social media, increasing activities outside so that they minimize opening social media, by turning off notifications so that they can focus on doing assignments or other things that are being done.